ANALISIS MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN IPS DI KELAS IV SDN 43 TAKKALA KOTA PALOPO - Sunardin, Sunardin (Program Studi Pendidikan Guru Sekolah Dasar Universitas Muhammadiyah Buton, 2021)
This study aims to analyze atudent leraning motivation in social studies subject. This type of research is a descriptive study using a quantitative appoarch. This resesach was conducted in takkalala public elementary schools palopo city. The source of data in this study were 20 students of grade IV takkalala public elementary schools. Data collection techniques used were quiestonairre techniques dan interview techniques. Student learning motivation data were obtained form filling out questionnaire sheets given to 20 students containing 21 statement items and interviews with class teachers. Then the data obtained were analyzed using descriptive statisyic. The result showed that average score of the processed data was72 with good category.